Statistical analysis of tensile strength and elongation of pulse TIG welded titanium alloy joints using Weibull distribution. Issue 1 (31st December 2016) - Balasubramanian, M.
Abstract: In this study, the tensile strength of a pulsed current tungsten inert gas welded Ti-6Al-4 V plate has been statistically analysed by Weibull distribution. Titanium alloy of 1.6 mm thickness was welded with pulsed current tungsten inert gas welding. Testing of mechanical properties was done to understand the influence of pulsing current on the fabricated joint. But the result obtained has to be consistent and repeatable. Hence, this paper investigates a method for predicting the reliability of values obtained for tensile strength and elongation with consistency. The tensile strength results obtained vary between 975 and 1160 MPa and percentage elongation vary between 2.4 and 5.9%. Using Weibull technique in conjunction with the experimental data, we can predict the output more accurately. Using Weibull distribution, the welded joint reliability can be obtained. The probability distribution according to which the joint will fail is estimated with the help of Weibull analysis.